National Crime Victimization Survey: Supplemental Victimization Survey, (United States), 2019 ([Verlag nicht ermittelbar], 2022)
The Supplemental Victimization Survey (SVS) data measure the prevalence of nonfatal stalking victimization among persons age 16 or older, the characteristics of stalking victims, and patterns of reporting to the police and other authorities so that policymakers, academic researchers, practitioners at the federal, state and local levels, and advocates can make informed decisions concerning policies and programs. The SVS also collects important characteristics of stalking such as the physical and emotional impact on victims, offender information, measures of self-protective actions, and the criminal justice system response. The SVS asks questions related to victims' experiences of unwanted contacts or behaviors during the previous 12 months. These responses are linked to the NCVS survey instrument responses for a more complete understanding of the stalking victim's circumstances. The 2019 SVS was the third administration of this NCVS supplement. The first SVS administration was in 2006. SVS releases from 2016 and after are not comparable to the 2006 SVS data because the survey instrument underwent a redesign with SVS 2016.